CORPORATE IDENTITY OF SHARIA HOTEL Studi Kasus: Implementation of Corporate Identity Hotel Aziza in Solo - Hartini, Sri (Transformasi, 2017)
This study aimed to describe and analyze the extent to which corporate idnetity of Aziza Hotelas a Sharia Hotel. The results of this study indicate that corporate identity is carried out byAziza Hotel includes the symbol of the company such as the name of company, logo, uniforms,colors and designs of buildings; behavior and also communications did. In its application,about the symbol, Aziza Hotel choose Islamic names, using a specific color choice. Aboutbehavior, Aziza Hotel emphasis on islamic services; and the last about the communications,Aziza Hotel implement a vision and mission that brought by the company.Key words: Implementation, Corporate Identity, Sharia Hotel